Marine recreational fishing in Portugal: current knowledge, challenges, and future perspectives - Diogo, Hugo (2021)
Marine recreational fishing (MRF) in Portugal is a traditional leisure activity with considerable importance for coastal populations. In the absence of available information from the national data collection framework, this article aims to review the existing information on MRF across the country. MRF was an open access fishery until recently, but with rising evidence of overexploitation of coastal resources, a precautionary approach was imposed topdown, without consulting recreational fishers. In Portugal, the MRF participation rate is comparable to the European average (2%). The most important fishing mode (according to the official issued licenses) is shore angling. Mainland Portugal marine recreational catches (0.8% of total commercial landings) are likely underestimated, while the estimate for the Azores (6% of total commercial landings) is probably closer to the national reality. The Portuguese MRF sector faces several challenges, including: (1) the need for a definition of a national data collection framework; (2) the inclusion of MRF harvest estimates in stock assessments for key captured species; (3) management approaches which also take into account the ecosystem approach to fisheries and any potential effects of climate change; (4) additional research on post-release mortalities for the most important MRF species; and (5) a stronger involvement of all stakeholders in the decision-making process of MRF. The latter would be critical to improve the adequacy of regulations to the MRF reality, mitigate conflicts with other sectors (e.g., commercial fishing), and potentially increase fishers compliance.